Influence of Government Performance, Accessibility of Financial Reports and the Financial Accounting System on Financial Report Accountability - Kharisma, Megania; Tajudin, Intan; Sarita, Rahma; Azzahra, Siti Fatimah (Santoso Academy Network, 2025)
This study aimed to examine how government performance, financial accounting systems, and financial report accessibility affect the accountability of financial reports in Palmerah Village. A quantitative research method was employed, using a sample of 47 respondents and data collection through questionnaires. The findings reveal that all three factors government performance, financial accounting systems, and report accessibility have significant and partial impacts on financial accountability. The study offers valuable implications for village officials and government institutions. Improving accountability requires enhancing the performance of government personnel through continuous training, implementing technology-based financial accounting systems, and ensuring public access to financial reports. These steps are vital for building public trust and promoting transparent and efficient financial governance at the village level. This research is original in its specific focus on Palmerah Village, a location rarely studied in the context of financial accountability. By addressing real-world challenges faced by local governments and the public's access to financial data, the study provides new empirical evidence and practical guidance. It contributes to better understanding and improving public sector governance in small-scale administrative units.